(untitled) (Revista de Investigaciones Universidad del Quindío, 2015)
This research was conducted with the purpose of estimating the vertical accuracy of the SRTM-30 MDT for Colombia. The MDT SRTM-30 was compared with three databases that were supplied by IGAC and IDEAM. For the calculation of the vertical accuracy were considered two scenarios, namely: general calculation and discriminated calculation that involved terrain slope. In addition to calculating statistics such as the mean error, the standard deviation and the root mean square, were also executed Test Koppe and Test NSSDA. While values obtained by Test NSSDA showed dependence with terrain slope, values from Test Koppe remained relatively stable in the two scenarios of calculation. With a confi dence level of 95% was determined a vertical accuracy of 17.0 m. Findings of the study are important to understand the error associated with SRTM-30 MDT and represents spatial characteristics of the error according to terrain slope. MDT SRTM-30 can be very useful for regional level study, further studies can be carried out to fi nd the vertical accuracy considering aspects such as land cover and terrain morphology.